2020
DOI: 10.1111/jam.14688
|View full text |Cite
|
Sign up to set email alerts
|

Immunosensor‐based rapid quantitative detection of Newcastle disease virus antibodies using innovative gold immunochromatographic assay

Abstract: Aims A novel quantitative method for rapid Newcastle disease virus (NDV) antibody detection was developed based on an innovative gold immunochromatographic assay with a quantitative immunosensor. Methods and Results NDV antibody‐detecting test strips containing a two‐reaction system and double‐test lines (T1, T2) were prepared. The test results were judged according to the signal ratio between the test and control lines as measured by the quantitative immunosensor. The minimum detection limit of the test strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Similar to avian influenza, ND can also be detected and diagnosed by using immunochromatographic assays. Recently, a quantitative antigen-based Au-immunochromatographic technique incorporated with viral protein antigens/AuNPs (haemagglutinin-neuraminidase) was developed, which allowed the detection of ND viral antibodies with a sensitivity of 2 2 titers without any cross-reactivity ( 42 ).…”
Section: Immuno-based Methodsmentioning
confidence: 99%
“…Similar to avian influenza, ND can also be detected and diagnosed by using immunochromatographic assays. Recently, a quantitative antigen-based Au-immunochromatographic technique incorporated with viral protein antigens/AuNPs (haemagglutinin-neuraminidase) was developed, which allowed the detection of ND viral antibodies with a sensitivity of 2 2 titers without any cross-reactivity ( 42 ).…”
Section: Immuno-based Methodsmentioning
confidence: 99%
“…Antibodies conjugated to NPs are more stable, biocompatible, and more sensitive to target antigens [ 12 ]. Effective bioanalytical kits of enzyme-linked immunosorbent assays (ELISAs) have been developed using nanomaterials to diagnose a number of animal infectious diseases, such as bird flu [ 13 , 14 , 15 , 16 ], post-weaning multisystem wasting syndrome (PMWS) caused by a porcine circovirus type 2 (PCV2) [ 17 , 18 ], Newcastle disease [ 19 , 20 , 21 ], and many others.…”
Section: Current Applications Of Nanomaterials In Veterinary Medicinementioning
confidence: 99%
“…The immune colloidal gold test strip has no cross-immune reaction with AIV, EDS, IB, and IBD which indicated that the test strips had high specificity and could specifically detect NDV antibodies. This method overcomes the limitation that the existing colloidal gold immunochromatographic method is only used for qualitative or semi-quantitative purposes ( 70 ). GICT technology is easy to operate and does not require other instruments.…”
Section: Serological Assaysmentioning
confidence: 99%